The phenomenon of xenophobia as experienced by immigrant learners in Johannesburg inner city schools - Krüger, Deirdré; Osman, Razia (Faculty of Education, University of the Free State, 2010)
This article aims to describe how xenophobia is experienced by a small selection of immigrant participants in five inner city schools in Johannesburg. The May 2008 xenophobic violence prompted the investigation. Theoretically, the article is also concerned with ways to combat xenophobia in schools with a view to bringing about fundamental social change aimed at deconstructing ‘anti-xenophobia education’, as the term has been coined. The methodology for the qualitative inquiry took the form of a triple-layered case study: the layers consist of the various groups of participants: immigrant learners, South African learners and educators. Sixteen semi-structured, in-depth interviews were conducted and the main method of data analysis was content analysis using Tesch’s (Creswell, 1994: 155) method of sorting the content of communications. The findings support the need for anti-xenophobia education in the schools under scrutiny. The immigrant participants reported very little compassion, rather humiliation and degradation in the form of unjust stereotyping, prejudice, bias and discrimination. Although cosmopolitanism featured, ‘otherness’ is far from being incorporated into an all-embracing ‘us’. Distrust between immigrant and South African learners emerged and both groups stereotyped the other as violent, although lack of trust and fear as pervasive issues seemed to underlie the stereotyping.
Keywords: Xenophobia; Inner city schools; Johannesburg; Anti-xenophobia education; Immigrant learners